Teknik dan media komunikasi kesehatan yang efektif dalam penyampaian informasi pencegahan dan vaksinasi COVID-19 pada remaja - Arif Nugroho Triutomo; Hasan Basri Borut (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Based on the survey results, the 17-30 year age group in carrying out the health protocol of washing their hands for 20 seconds with soap was only 66.0%, in contrast to the 46-60 year age group and > 60 years reaching > 80%. The young age group is also a group that is more confident that it is unlikely to be infected with the COVID-19 virus, reaching 20.2%, in contrast to the 31-45 year old group, which only 15.4% stated that it was very unlikely to be infected with the COVID-19 virus. The output target of this community service program is to increase and increase adolescent knowledge about how to prevent and vaccinate COVID-19 and to be able to disseminate information about prevention and vaccination of COVID-19. The method used in community service activities, especially youth at the Mantrijeron Ministry is the socialization method regarding the introduction of effective communication media in delivering information on COVID-19 Prevention and Vaccination to adolescents. The result of this community service is the BERANI Poster "Bersama Remaja Tangani Pandemi" for youth at the Mantrijeron Ministry of Education which can be used for socialization in the community both through print media and social media. The spread of COVID-19 until the beginning of 2021 in the world tends to continue to increase from time to time, causing greater casualties and material losses, and has implications for social, economic, and community welfare aspects. Based on the results of the Central Statistics Agency (BPS) survey on Community Behavior during the COVID-19 Pandemic, young people are the group that is more difficult to implement health protocols or accept health ideas related to COVID-19. This community service activity aims to increase youth's knowledge of how to prevent and vaccinate COVID-19 and can produce graphic designs about effective information media for youth at the Mantrijeron Islamic School about COVID-19 prevention and vaccination. The method used in community service activities, especially youth at the Mantrijeron Ministry of Education is the socialization method about COVID-19 and COVID-19 Vaccination and the introduction of effective communication media in delivering information on COVID-19 Prevention and Vaccination to adolescents. Although this community service activity has been simulated with learning videos about making health promotion media, due to limited equipment (computers/laptops) for participants, it is necessary to carry out further tutorials related to making health promotion media.